1965
DOI: 10.1177/070674376501000302
|View full text |Cite
|
Sign up to set email alerts
|

Caprice: The ‘COOL’ Rebellion

Abstract: Our present age has contributed a ‘new’ factor to the historical dialogue between the forces of rebellion and the status quo. From many sources movements have arisen which have in common non-predictability. In mathematics this is known as the non-linear relationship, in literature the non-novel, in drama the theatre-of-the-absurd, and in physics and philosophy the ‘uncertainty principle’. In psychotherapy, particularly of adolescents, there is often seen a remarkable capricious wilfulness which, rich in irony,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Prior research suggests that there is content to coolness beyond mere likability and desirability. Youthfulness (Martino, 2000), sexual appetite (Strodtbeck, Short, & Kolegar, 1962), risk taking (Martin & Leary, 2001), toughness (Aloise-Young & Hennigan, 1996;Denborough, 1996;Rodkin, Farmer, Pearl, & Van Acker, 2000), masculinity (Czopp, Lasane, Sweigard, Bradshaw, & Hammer, 1998;Denborough, 1996;Martino, 2000), muted emotion (Beckerleg, 2004;Erber, Wegner, & Therriault, 1996), rebelliousness (Eggertsen, 1965), and rejection of effortful striving (Czopp et al, 1998;Osborne, 1999;Williams, Burden, & Lanvers, 2002) are all presumed to be cool in contemporary Western cultures. The valuation of coolness has also been linked to bullying, gang membership, and interpersonal violence (Denborough, 1996;Houndoumadi & Deree, 2001;Strodtbeck et al, 1962), as well as to smoking and drug use (Griffin, Epstein, & Botvin, 2001;Martin, & Leary, 2001;Plumridge, Fitzgerald, & Abel, 2002).…”
Section: Colloquial Coolness and A Lexical Perspectivementioning
confidence: 99%
“…Prior research suggests that there is content to coolness beyond mere likability and desirability. Youthfulness (Martino, 2000), sexual appetite (Strodtbeck, Short, & Kolegar, 1962), risk taking (Martin & Leary, 2001), toughness (Aloise-Young & Hennigan, 1996;Denborough, 1996;Rodkin, Farmer, Pearl, & Van Acker, 2000), masculinity (Czopp, Lasane, Sweigard, Bradshaw, & Hammer, 1998;Denborough, 1996;Martino, 2000), muted emotion (Beckerleg, 2004;Erber, Wegner, & Therriault, 1996), rebelliousness (Eggertsen, 1965), and rejection of effortful striving (Czopp et al, 1998;Osborne, 1999;Williams, Burden, & Lanvers, 2002) are all presumed to be cool in contemporary Western cultures. The valuation of coolness has also been linked to bullying, gang membership, and interpersonal violence (Denborough, 1996;Houndoumadi & Deree, 2001;Strodtbeck et al, 1962), as well as to smoking and drug use (Griffin, Epstein, & Botvin, 2001;Martin, & Leary, 2001;Plumridge, Fitzgerald, & Abel, 2002).…”
Section: Colloquial Coolness and A Lexical Perspectivementioning
confidence: 99%
“…The constitution of cool in our study was found to be different in several ways. The western ideas of cool have been found to be associated with social acceptance, aggression and resistance to bullying (Graham and Juvonen, 2002); private rebellion and pleasure seeking (Pountain and Robins, 2000); rebelliousness (Eggertsen, 1965); confidance (Charles, 2002); youthfulness (Martino, 2000); masculinity (Czopp et al , 1998); and little divergence away from the normal (Warren and Campbell, 2014). However, “cool” discovered in this study converged with the Western cool with respect to calm disposition or being emotionally neutral (Stearns, 1994); possessing composure in stressful situations (Majors and Billson, 1993); and way of appearance and conversation (Gioia, 2009).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…People who are accepted, show aggression and are not victimized are perceived as cool (Graham and Juvonen, 2002). The traits connected to cool include emotional neutrality (Stearns, 1994), poise in stress (Majors and Billson, 1993), authenticity (Southgate, 2003), private rebellion and pleasure seeking (Pountain and Robins, 2000), confidence (Charles, 2002), masculinity (Czopp et al , 1998), rebelliousness (Eggertsen, 1965) striving effortlessly (Osborne, 1999), muted emotion (Beckerleg, 2004), youthfulness (Martino, 2000), daring (Martin and Leary, 2001), and aggressive and pro-social (Rodkin et al , 2000). Being true to oneself and being authentic are also described as the trademarks of cool behavior (Southgate, 2003).…”
Section: Facets Of Coolmentioning
confidence: 99%